2022
DOI: 10.4070/kcj.2021.0321
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor Monotherapy After 3-Month Dual Antiplatelet Therapy in Acute Coronary Syndrome by High Bleeding Risk: The Subanalysis From the TICO Trial

Abstract: Author's summary This study demonstrated that for acute coronary syndrome patients treated with drug eluting stents, high bleeding risk (HBR) was associated with higher rates of net adverse clinical events (NACEs), not only including bleeding but also ischemic events. Ticagrelor monotherapy after 3-month dual antiplatelet therapy (DAPT) was associated with lower rates of NACEs and major bleeding than ticagrelor-based 12-month DAPT regardless of HBR, with no significant interaction between therapy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The remaining 4 RCTs (TWILIGHT, 17 SMART-CHOICE, 18 REDUCE, 19 and TICO 20 trials) compared 3-month DAPT with standard DAPT. Furthermore, GLOBAL LEADERS, STOPDAPT-2, 21 TWILIGHT, 22 and TICO 23 analyzed the duration of DAPT in patients at HBR.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 4 RCTs (TWILIGHT, 17 SMART-CHOICE, 18 REDUCE, 19 and TICO 20 trials) compared 3-month DAPT with standard DAPT. Furthermore, GLOBAL LEADERS, STOPDAPT-2, 21 TWILIGHT, 22 and TICO 23 analyzed the duration of DAPT in patients at HBR.…”
Section: Resultsmentioning
confidence: 99%
“…[18] A study in Korea (TICO) revealed that the incidences of NACEs and major bleeding were lower in patients with ACS undergoing PCI that were treated with ticagrelor monotherapy after 3 months of DAPT compared with those in patients treated with ticagrelor-based 12-month DAPT, and the effects were more prominent in patients with a high risk of bleeding. [19] In addition, the HOPE-TAILOR trial provided valuable information on a de-escalation strategy using half-dose prasugrel and ticagrelor in East Asian patients with ACS. The patients were pragmatically randomized to either prasugrel, ticagrelor, or clopidogrel groups, followed by a half-dose reduction at 1 month, or a conventional dose of 75 mg clopidogrel.…”
Section: Discussionmentioning
confidence: 99%
“…The main results of the TICO trial have been shown to be consistent in several subgroup analyses such as DM status [ 73 ], high-ischemic risk [ 74 ], ST-segment elevation myocardial infarction (STEMI) [ 75 ], and HBR status [ 76 ]. A complete list of the prespecified and post-hoc analyses performed by the TICO investigators are shown in Table S3 .…”
Section: P2y 12 Monotherapy Versus Dapt After Pcimentioning
confidence: 99%